Iran : economic development under dualistic conditions - Amuzegar, Jahangir; Fekrat, M. Ali (Chicago ; London : University of Chicago Press, 1971)
This is study of economic development in Iran covering 1910-1950 to 1972. It covers topics like: paths of growth; oil and the Iranian economy 1910-1950; oil and the Iranian economy 1950-1972; achievements and drags; good luck and designs. The study provides insight on basic factors responsible for economic progress in dualistic economies like Iran.
Includes bibliographical references and index.
lje 28/09/2018
Loans
Keywords: Petroleum industry and trade; Iran